الصفاتُ النفسية في قصةِ موسى عليه السلام في سورة القصص = Psychological characteristics in the story of Moses, peace be upon him, in Surat Al-Qasas - Mohammed Saeed, Nasr Baggash; Abdo Khaled, Nashwan (IIUM Press, 2024)
The research describes the psychological characteristics of Prophet Moses, peace be upon him, based on Surat Al-Qasas, describing the circumstances of Moses peace be upon him and those with him at the time of their weakness. All the consolation was given to him and the good news of the end of disbelief, the demise of the unbelievers, and the imminent conquest of Mecca. Psychological characteristics may be hereditary or acquired, distinguishing an individual from others, and they can only be observed through behavior or various situations, and they are usually permanent or semipermanent. The psychological and behavioral qualities and what they mean in terms of chastity are nothing but patience to abandon forbidden desire, and what they mean in terms of wisdom is patience with a person’s stubbornness and harm in return, and sincerity is patience in fulfilling the covenant in terms and conditions, and what compassion means is his sacrifice for the sake of his people and confronting tyranny. Pharaoh in order to save them from hell. Mercy is the strongest or kindest mercy, and it almost never leads to hatred, and mercy may fall into hatred for the sake of interest. Muslim educational scholars must understand it well, and work to build the psychological aspects of the nation and how to reform them through methodological and pedagogical tasks, and ensure that everything presented to young people is appropriate to their stages of development, and instills in them positivity. Psychological qualities and energies that drive them to self-confidence and the desire to perform. Their mission in life and pride in it.